Differences in bird and bat traits, seed-dispersal interactions and functions between tropical montane forest and bracken-dominated areas - Mayta, Cesar; Schleuning, Matthias; López, Cecilia L.; Villegas, Mariana; Hensen, Isabell; Gallegos, Silvia C. (Frontiers in Ecology and Evolution, 2025)
Most tropical plant species depend on animals to disperse their seeds. Seed dispersal by animals allows plants to colonize new sites in deforested habitats helping to accelerate forest recovery. However, deforestation can affect the interactions between animals and plants that are crucial for forest regeneration. In this study, we analyze the differences on the composition of functional traits and on seed-dispersal interactions and functions by birds and bats between forest and deforested areas dominated by bracken fern. At eight study sites, we captured birds and bats in bracken-dominated areas and at forest in the tropical montane forest of Bolivia and analyzed their droppings. We found a similar composition of functional traits related to animal size, gape width and degree of frugivory of bats in both habitat types. Hand-wing index of birds was significantly higher in bracken compared to forest. Birds had more interaction richness and abundance in bracken than in forest, and bats had more interaction abundance in forest than in bracken. The majority of seeds dispersed by birds and bats in bracken were from pioneer species. We conclude that, although seed dispersal by birds and bats is maintained in the bracken-dominated areas, most of the dispersed seeds belong to pioneer species. Pioneer species are unlikely to establish in bracken-dominated areas, making the natural regeneration process of these deforested areas very slow.